A corpus-based interpretation of the discourse–cognitive–society triangle on Chinese court judgments - Jingjing Wu; Le Cheng; Yi Yang (Humanities & Social Sciences Communications, 2022)
Abstract A court judgment is a common legal discourse and the final carrier of court trial activities. From the perspective of socio-cognitive discourse analysis, this study aims to describe and explore the Chinese court judgments in a corpus-based method, concentrating on the interactions among discourse, cognitive, and social dimensions. We have three key findings through an empirical qualitative analysis of the court judgments in China. First, the discourse dimension of Chinese court judgments is both society-oriented and cognition-oriented. The discourse components could mark the cognition sources in court judgments. Second, the cognitive source of faith is a part of social cognition on law and regulation, and induction and paraphrase provide the personal cognition to testimony, documentary, or hearsay evidence. Besides, the cognitive source of inference could change personal cognition into a social consensus through a reasoning process. Third, the social function of court judgments corresponds to the cognitive source and builds the surface structure with various discourse components. Moreover, a probe into the multi-dimensional relationship in court judgments can offer practical insights into the interpretation of legal texts in Chinese judicial decision-making.